Going beyond structured observations: Looking at classroom practice through a mixed method lens - Lindorff, A; Sammons, P (Springer Verlag, 2018)
In this paper, we extend a mixed method (MM) approach to lesson observation and analysis used in previous research in England, combining multiple structured observation instruments and qualitative field notes, to provide a framework for studying three videotaped lessons from 3rd-grade US mathematics classrooms. Two structured observation schedules are employed, one subject-specific and research-oriented and the other generic and inspection-oriented. Both instruments were previously developed based on evidence from the teacher effectiveness research (TER) knowledge base. Qualitative field notes, in addition to structured observation schedules, provide detailed narratives for each lesson video. Separate findings from each instrument and approach are presented, followed by an integrated analysis and synthesis of results. Although previous studies used similar methods to analyze teaching practice within broader research designs incorporating additional methods and perspectives (e.g. teacher interviews, pupil assessments, pupil questionnaires), this paper explicitly examines the strengths and limitations of the multi-instrument, mixed method approach to lesson observation. Using multiple observation instruments allows for triangulation as well as consideration of complementary foci (i.e. a content-specific instrument measures fine-grained aspects of practice not emphasized in a more generic instrument, and vice versa). Field notes facilitate rich descriptions and more thorough contextualization and illumination of teaching practice than structured observation ratings alone. Further, the MM approach allows for consideration of lesson features beyond those established in TER literature as sufficient to characterize ‘effective’ practice.